Masa Keemasan pada Seni dan Arsitektur Masa Daulah Abbasiyah - Sri Hastuti; Hanifa Rahmatunnisa; Aidil Fitra Lubis; Achmad Maftuh Sujana (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Islam after the death of the Prophet Muhammad SAW experienced a golden age. The peak of this glory was not seen from the size of its territory, but from the progress of various sectors such as art, culture, building architecture, and education. All of this success was achieved during the Abbasid Dynasty. This dynasty was different from the previous empire, namely the Umayyad, which focused more on expanding the territory of da'wah. In this short and simple article, the development of art, especially architecture, during the Abbasid Dynasty is discussed, which is one indicator of the progress of the Baghdad Caliphate. Architecture is the work of an architect designed to build spaces in a building with certain functions and purposes. The royal palace building is an architectural design that is formed according to the development of the times and contains certain meanings in each of its arrangements. This article aims to explain the architectural style of the Abbasid Caliphate palace, including its types and the influence of other architectural styles in its construction. The method used is a literature study (library research) by collecting data from various relevant literature. The results of this writing are expected to provide a general description of the characteristics of palace architecture during the Abbasid Dynasty.